(untitled) (Palimpsesto, 2018)
This paper we propose a reading relative to the movement of “pobladores” from Santiago in terms ofchange and continuity taking as a temporal-axis the 1982 and 1999 years, that is, between civic-militarydictatorship and democracy in Chile. By way of hypothesis we intend to point out that the landings duringthe 90s’ harmonize occupational actions with the "collective postulation" which implies the insertion ofthe “pobladores” world towards neoliberal logics in the ways of obtaining housing and, on the other hand,During the democratic transition, there is a crisis of the traditional parties referents, opting for theapproach to grassroots political parties or organizational referents with preferential social rather thanpolitical overtones.